MARITIME QUR’ANIC INTERPRETATION IN COASTAL RITUALS: A CASE STUDY OF THE SEA OFFERING TRADITION IN MADURA - Bakir, Moh.; Ludfi, Ludfi; Kahar, Abd. (Universitas Nurul Jadid, 2024)
The phenomenon of religious-cultural syncretism in Indonesia’s coastal communities remains underexplored within the framework of living Qur’an studies, especially regarding the interpretation of maritime Qur’anic verses in local ritual practices. The sea offering tradition (sedekah laut) in Pamekasan, Madura, represents an actualization of Islamic values intertwined with local wisdom; however, its direct connection to Qur’anic maritime verses has yet to be thoroughly investigated. This study aims to explore how the fishing communities in Pamekasan interpret and actualize the values of maritime Qur’anic verses in the context of the sea offering ritual. A qualitative ethnographic approach was employed through participant observation, in-depth interviews with religious leaders and fishermen, and document and classical tafsir analysis. The findings reveal that the sea is perceived as a manifestation of Allah’s greatness, a source of sustenance, and a test of faith that must be honored and preserved. The sea offering ritual functions as a symbolic integration of Islamic teachings and local cultural practices, strengthening both social solidarity and ecological awareness. Verses such as QS. Al-Furqān (25): 53, Al-Mulk (67): 15, Al-Nahl (16): 14, and Al-A’rāf (7): 163 are contextualized through the combination of prayers and cultural symbols, including bitek (miniature boats made of banana trunks) and seven-colored flowers. This study contributes significantly to the advancement of contextual Qur’anic interpretation and Islamic anthropology by highlighting the dynamic integration of sacred texts and local cultural practices. The findings are expected to serve as a reference for developing a more adaptive model of contextual exegesis that aligns with social realities and the preservation of Islamic-based local traditions.